Improvement of direct torque control applied to doubly fed induction motor under variable speed - Hala Alami Aroussi; Elmostafa Ziani; Manale Bouderbala; Badre Bossoufi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This work is dedicated to the study of an improved direct torque control of the doubly fed induction motor (DFIM). The control method adopts direct torque control 'DTC' because of its various advantages like the ease of implementation which allows a good performance at transient and steady state without PI regulators and rotating coordinate transformations. To do this, the modeling of the motor is performed. Subsequently, an explanation of the said command is spread out as well as the principle of adjusting the flux and the electromagnetic torque according to the desired speed. Then, the estimation method of these two control variables will be presented as well as the adopted switching table of the hysteresis controller model used based on the model of the multilevel inverters. Finally, the robustness of the developed system will be analyzed with validation in Matlab/Simulink environment to illustrate the performance of this control.